Perancangan Galeri Fotografi Dengan Pendekatan Arsitektur Metafora - Nazamri Nazamri; Gun Faisal; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The photography gallery is a place to accommodate the work, a place to hold exhibitions, entertainment and recreation. But in the city of Pekanbaru did not have a container to realize the activity. The development of photography continues to improve based on the community and photography enthusiasts, so it is a gallery of photography in Pekanbaru. Photographic gallery with a metaphorical architectural approach which has the formation of the camera as a form of building. Meanwhile, the basic concept of building ideas is